The new paradigm of heritage and its consideration regarding landscapes: Concepts, methods and prospective evolution - Silva Pérez, Rocío; Fernández Salinas, Víctor (Documents d’Anàlisi Geogràfica, 2017)
This article explores the landscape-heritage-territory debate from the perspective of heritage as a social and institutional attribution of values and the territorial and typological complexity of heritage landscape. A conceptual and methodological approach to these landscapes is proposed, focusing on landscape stakeholders and their appreciative dynamics (“heritagisation” processes), as well as on the elements and arguments around which social and institutional identification coalesce with landscapes (heritage vectors). The article proposes an empirical transfer that exemplifies landscapes with different dominant features and on different scales, and concludes with a critical evaluation of the instruments used in the institutional recognition of heritage and landscape management, addressing their potentials and limitations.